Integrating Augmented Reality (AR) in Learning to Increase Student Engagement - Tarsono; Saadah, Susi; Fitriya, Erma; Aldi, Ujang; Darojat; Khotimah, Imas; Naufal Abdillah (International Journal of Community Engagement Payungi, 2025)
The quality of education is largely determined by the level of active participation of students in the learning process. Unfortunately, many conventional teaching methods still rely on one-way delivery of material, which makes students less interested and have difficulty understanding the material thoroughly. To answer this challenge, Augmented Reality (AR) technology comes as an innovation that can create a more lively and interactive learning atmosphere. AR presents learning content in the form of three-dimensional visuals that can be seen and explored directly by students, so that learning becomes more fun, immersive, and easy to understand. This research examines how the use of AR can increase student engagement in the digital era through a qualitative approach by reviewing various studies and scientific literature. The results show that AR can increase learning motivation, concept understanding, and cooperation skills. AR is also flexible in adjusting students' diverse learning styles and supporting inclusive learning. However, AR implementation faces obstacles such as limited devices, infrastructure, and teacher readiness. Therefore, integrative strategies and support from various parties are needed so that the implementation of AR can run effectively and become a sustainable educational transformation tool.